Sin señas particulares (2020) – espacios, tiempos y tramas de la distopía y lo in/posthumano en la frontera México-EEUU - Karen Genschow (Moderna Språk)
The film Sin señas particulares (2020) is set in a dystopian landscape in northern Mexico, devastated by the drug trafficking and gang violence that has taken possession of vast territories of the country, in which a mother searches for her son. The protagonist will encounter within this scenario not only the liminal space of the border, that separates and at the same time unites the here and there sides of the colonial order, but also with the limits of that same order which, with its “conditions of extreme mortality” (Rivera Garza), governed by necropolitics (Mbembe), presents itself as the dark reverse of the humanist conception (Braidotti) and points towards an end of humanism in order to make room for other ways of thinking and living the world, though in the modality of dystopia.